2014
DOI: 10.1002/pola.27372
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and evaluation of a polymeric gel containing ionic liquid-functionalized MWCNTs as a novel class of organic solvent absorbent

Abstract: Multiwalled carbon nanotubes grafted with vinyl immidazolium‐based ionic liquid (MWCNT‐IL) were synthesized and utilized as a crosslinking agent for the preparation and evaluation of a polymeric gel as a new class of organic solvent absorbent. Based on our earlier organic solvent‐absorbents, the present polymeric gel exhibited high organic solvent absorbency, fast organic solvent absorption rate, and good reusability. To prepare such polymeric gel, radical polymerization was carried out with dodecyl methacryla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 61 publications
1
1
0
Order By: Relevance
“…) clearly show round Co present at moderately high density and with fairly even, non‐ordered distribution along the walls and at the ends of nanotubes. Very similar morphology observations have been previously reported . Inductively coupled plasma atomic adsorption emission (ICP‐OES) analyses indicate 55.3 wt% of Co is deposited onto the Co‐IL‐MWCNT corresponding to 87.8% of the Co used.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…) clearly show round Co present at moderately high density and with fairly even, non‐ordered distribution along the walls and at the ends of nanotubes. Very similar morphology observations have been previously reported . Inductively coupled plasma atomic adsorption emission (ICP‐OES) analyses indicate 55.3 wt% of Co is deposited onto the Co‐IL‐MWCNT corresponding to 87.8% of the Co used.…”
Section: Resultssupporting
confidence: 84%
“…The measurements were carried out in the range 30–800°C with a ramp of 10°C min −1 in air. The catalyst sample decomposes in two major steps . It is observed that adsorbed IL starts to degrade at a lower temperature compared to neat IL, which may be due to changes in the IL structure as a result of the interaction with CNTs and the presence of Co NPs on CNT surface .…”
Section: Resultsmentioning
confidence: 99%